2014
DOI: 10.1016/j.amjcard.2014.05.068
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Clinical Correlates, and Functional Impact of Subaortic Ventricular Septal Bulge (from the Baltimore Longitudinal Study of Aging)

Abstract: A localized hypertrophy of the subaortic segment of the ventricular septum - ventricular septal bulge (VSB) - has been frequently described in series of elderly persons, but its prevalence with age, clinical correlates and impact on cardiac function and exercise capacity remain uncertain. We explored these associations in a cross-sectional sample without known cardiac disease from the Baltimore Longitudinal Study of Aging. We randomly selected 700 participants (50% men, mean age 64±15, range 26–95 years) and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 26 publications
3
31
0
9
Order By: Relevance
“…Indeed, in contemporary adult HCM populations, prevalence of hypertension ranges from 20% to 60% 20 21 23 25–29. The prevalence of hypertension in VSB observational studies ranges between 50% and 80%,1 14 15 thus slightly higher than that reported in HCM studies. However, considering that a conclusive independent association between hypertension and VSB has yet to be confirmed,1 14–16 a history of hypertension is currently of little help in differentiating VSB from HCM.…”
Section: Demographics and Medical Historymentioning
confidence: 59%
See 4 more Smart Citations
“…Indeed, in contemporary adult HCM populations, prevalence of hypertension ranges from 20% to 60% 20 21 23 25–29. The prevalence of hypertension in VSB observational studies ranges between 50% and 80%,1 14 15 thus slightly higher than that reported in HCM studies. However, considering that a conclusive independent association between hypertension and VSB has yet to be confirmed,1 14–16 a history of hypertension is currently of little help in differentiating VSB from HCM.…”
Section: Demographics and Medical Historymentioning
confidence: 59%
“…Patients with VSB did not display a sex preference,1 14 15 in contrast to HCM, which has been generally characterised by a 3:2 male predominance,6 at least at younger ages 20 21. A recent review of 969 consecutive American and Italian patients with HCM demonstrated a reversed 60% versus 30% female predominance only in patients older than 60 years of age 22.…”
Section: Demographics and Medical Historymentioning
confidence: 86%
See 3 more Smart Citations